An Out-of-plane Loaded Double Cantilever Beam (ODCB) test to measure the critical energy release rate in mode III of adhesive joints. (June 2018) - Loh, Lukas; Marzi, Stephan
Abstract: A novel fracture mechanical test for adhesive joints subjected to pure mode III loading is presented. The experiment uses a modified double cantilever beam specimen, which is loaded out of the plane of crack propagation. The paper presents and discusses first experimental results, applying the new test method on adhesively bonded joints of an elastic-plastic structural adhesive. The tests have been performed under quasi-static load conditions. Beside the critical energy release rate, the test gives information about the total shape of the corresponding Traction-Separation-Law at the location of the initial crack tip. The calculation of the critical energy release rate is done by two different analytical approaches. Firstly, an evaluation method based on the Irwin-Kies equation is proposed, which is strictly valid for Linear-Elastic Fracture Mechanics conditions only and which is commonly used in case of classical Double Cantilever Beam tests. The second approach deals with a calculation of the J-integral, which holds for non-linear fracture behavior as well. The two evaluation methods are applied to experimental results of the new test method; the differences between both methods are pointed out and discussed. Additionally, the obtained test results in mode III are compared to equivalent results from mode II tests, which are taken from literature to proof a possible correlation between the shear crack opening modes II and III.